The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. IV. Contribution to the knowledge of subtribes Hoplitoxenina and Dimerometopina with description of a new species of Hadrophorus Fairmaire, 1898 - Hlaváč, Peter; Nakládal, Oto (Zootaxa, 2016)
The subtribe Dimerometopina Célis, 1970 is reestablished. A key and catalogue of the species of subtribes Hoplitoxenina and Dimerometopina is provided; a key to species of the genus Hadrophorus Fairmaire, 1898 is also given. Hadrophorus martinkae sp. n. from Madagascar, Montagne d’Ambre is described. New records for Hadrophorus spinipennis Célis, 1969 (Madagascar, Zombitse N.P.) and Hoplitoxenus joannae Jeannel, 1960 (Cameroon and Gabon, first record) are provided.